Analisis Literatur tentang Implementasi Hukum dan Tantangan Pembiayaan Mudharabah dalam Perbankan Syariah - Eri Zulfahmi; Rita Lilisdar; Pretty Ferdianti; Rika Auliani Safitri; Darlin Rizki; Muliza (Sekolah Tinggi Agama Islam Az-Zain Sampang, 2024)
This study examines the implementation and challenges of mudharabah financing in Islamic banking through a systematic literature review. Mudharabah financing is an important Islamic financial instrument, but its implementation still faces various obstacles. Using thematic analysis of relevant articles, journals and books, this study aims to identify common challenges and best practices in the implementation of mudharabah. The results are expected to provide a comprehensive insight into the obstacles faced by Islamic banks in implementing mudharabah financing, as well as strategies that have proven effective in overcoming these challenges. The findings can serve as a reference for practitioners and policy makers in optimizing the role of mudharabah financing in the Islamic banking sector.